Numerical simulation of aneurysmal haemodynamics with calibrated porous-medium models of flow-diverting stents. (26th October 2018) - Li, Yujie; Zhang, Mingzi; Verrelli, David I.; Chong, Winston; Ohta, Makoto; Qian, Yi
Abstract: Modelling flow-diverting (FD) stents as porous media (PM) markedly improves the efficiency of computational fluid dynamics (CFD) simulations in the study of intracranial aneurysm treatment. Nonetheless, the parameters of PM models adopted for simulations up until now were rarely calibrated to match the represented FD structure. We therefore sought to evaluate the PM parameters for a representative variety of commercially available stents, so characterising the flow-diversion behaviours of different FD devices on the market. We generated fully-resolved geometries for treatments using PED, Silk+, FRED, and dual PED stents. We then correspondingly derived the calibrated PM parameters—permeability ( k ) and inertial resistance factor (C2 )—for each stent design from CFD simulations, to ensure the calibrated PM model has identical flow resistance to the FD stent it represents. With each of the calibrated PM models respectively deployed in two aneurysms, we studied the flow-diversion effects of these stent configurations. This work for the first time reported several sets of parameters for PM models, which is vital to address the current knowledge gap and rectify the errors in PM model simulations, thereby setting right the modelling protocol for future studies using PM models. The flow resistance parameters were strongly affected by porosity and effective thickness of the commercial stents, and thus accounted for in the PM models. Flow simulations using the PM stent models revealed differences in aneurysmal mass flowrate (MFR) and energy loss (EL) between various stent designs. This study improves the practicability of FD simulation by using calibrated PM models, providing an individualised method with improved simulation efficiency and accuracy.